Penerapan User Centered Design untuk Optimisasi User Experience Aplikasi Virtusee - Nabila Octavianti; Rizka Hadiwiyanti; Abdul Rezha Efrat Najaf (Jurnal Teknologi Informasi dan Multimedia, 2025)
This study aims to redesign Virtusee, an employee performance monitoring platform, using the User-Centered Design (UCD) methodology. Virtusee features functionalities such as leave requests, monthly performance tracking, and self-service payslip access. The application, last updated in 2014, was described by users as outdated and not aligned with current trends. Based on the System Usability Scale (SUS) questionnaire, the application scored 40, categorized as poor with a grade of F, indicating the need for significant improvements. Employing the UCD approach, this study prioritized user needs and preferences in the redesign process, following these stages: (1) defining the usage context, (2) identifying user and organizational requirements, (3) design and implementation, and (4) usability evaluation. Testing the new design involved users who had used Virtusee more than once in the past month. The testing scenarios included exploring the new design, completing SUS and QUIS (Questionnaire for User Interaction Satisfaction) surveys via Google Forms, and conducting brief interviews to gather suggestions and critiques. Data were collected through observation, interviews, literature review, and questionnaire dissemination. Results showed a significant improvement, with the SUS score increasing to 80.3, indicating acceptable usability. The QUIS evaluation revealed average scores ranging from 5.9 to 6.8 across various indicators, exceeding the expected median. These findings highlight that the UCD methodology is effective in designing applications that are more user-centered, enhancing productivity and user satisfaction. This study provides valuable insights for developers aiming to create applications that are not only functional but also adaptive to evolving user needs, serving as a reference for designing solutions that align with user-centric principles.